The Visual Creativity of Protests in Romania (2016-2019) - Horvath, Gizela (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
After the pictorial turn, it is not surprising that political messages are more and more often presented in a visual form. Today, the battle between great ideas is not only fought via texts, but also through real and virtual images, or, through imagetexts. This paper tackles the image politics of the Romanian post-2016 anti-government popular resistance through some typical cases of imagetext: hashtags, symbols, video mapping, posters and some cases of visible space-occupation. These examples can present the anonymous (in some cases professional) artistic creativity, which helps the formation of social solidarity and crystallizes the message of the resistance.